Tanggung Jawab Notaris atas Kelalaian Memeriksa Status Hukum dalam Pembuatan Akta Pengalihan Hak Paten yang Telah Gugur - Siti Rahmah; Anang Shophan Tornado (Lembaga Yasin AlSys, 2026)
Although notarial responsibility has received attention in various legal studies, research that specifically discusses notarial negligence in verifying the legal status of expired intellectual property rights, particularly patent rights, remains limited. This study aims to analyze whether a notary can be deemed negligent if they fail to examine the legal status of a lapsed patent right before preparing a deed of transfer and to examine the legal consequences arising from such negligence. This study used a normative legal research method with statutory, conceptual, and analytical approaches. The legal materials used consisted of primary legal materials in the form of Law Number 2 of 2014 concerning Notary Position, Law Number 13 of 2016 concerning Patents, the Indonesian Civil Code, as well as relevant legal regulations and doctrines. The data were analyzed prescriptively using the theory of fault, the theory of legal protection, the theory of negligence, the theory of prudence, and the theory of legal events. The results show that a notary can be deemed negligent if they do not verify the legal status of the patent right that becomes the object of transfer because a notary is required to act honestly, carefully, independently, and with full prudence in carrying out their office. Examining the legal status of a patent right is part of the application of the principle of prudence to ensure that the right being transferred remains valid and can become the object of a legal act. Negligence in such verification has implications for the notary’s legal liability and has the potential to weaken legal certainty in patent right transfer transactions. The conclusion of this study emphasizes the importance of verifying legal status before preparing a deed of transfer of patent rights. These findings provide a theoretical contribution to the development of the literature on notarial law and intellectual property law, as well as practical implications for notaries, legal practitioners, and policymakers in strengthening legal certainty in intangible asset transactions.